PENGARUH MODEL THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS VIII SEMESTER GENAP SMP ADVENT BANDAR LAMPUNG - Haryanto, Haryanto; Kirana, Arinta Rara (STKIP PGRI Bandar Lampung, 2019)
The purpose of this research is to find the learning modelThink Pair Share (TPS) with the ability to communicate math at grade student viii even junior high school advent bandar lampung in year 2016/2017. Methods used in this research is the experimental methods using learning model Think Pair Share on class experiment and conventional kind on control class. As for the population of the research is all students viii even junior high school advent Bandar Lampung in year 2016/2017. Sample used were students class viii b as a class experimentation and class viii c as a class control. Sample using a technique to determine research clusters random sampling.The instrument used an essay test.Statistics with data analysis using formulas t-tes. The results of research and analysis of data is collected the value of thit = 5,60 and from the table the distribution of the first 5 % known tdaf = 2 then obtained thit > tdafso it will be concluded that there is the influence of “learning model think pair share ( tps ) on ability communication math class students viii even junior high school advent bandar lampung in year 2016/2017”.